Motor Alterations Induced by Chronic 4-Aminopyridine Infusion in the Spinal Cord In vivo: Role of Glutamate and GABA Receptors - Lazo-Gómez, Rafael; Tapia, Ricardo (Frontiers in Neuroscience, 2016)
Motor neuron degeneration is the pathological hallmark of motor neuron diseases, a group of neurodegenerative disorders clinically manifested as muscle fasciculations and hyperreflexia, followed by paralysis, respiratory failure and death. Ample evidence supports a role of glutamate-mediated excitotoxicity in motor death. In previous work we showed that stimulation of glutamate release from nerve endings by perfusion of the K+-channel blocker 4-aminopyridine (4-AP) in the rat hippocampus induces seizures and neurodegeneration, and that AMPA insusion in the spinal cord produces paralysis and motor neuron death. On these bases, in this work we have tested the effect of the chronic infusion of 4-AP in the spinal cord, using implanted osmotic minipumps, on motor activity and on motor neuron survival, and the mechanisms underlying this effect. 4-AP produced muscle fasciculations and motor deficits assessed in two motor tests, which start 2-3 h after the implant, which ameliorated spontaneously within 6-7 days, but no neurodegeneration. These effects were prevented by both AMPA and NMDA receptors blockers. The role of GABAA receptors was also explored, and we found that chronic infusion of bicuculline induced moderate motor neuron degeneration and enhanced the hyperexcitation produced by 4-AP. Unexpectedly, the GABAAR agonist muscimol also induced motor deficits and failed to prevent the MN death induced by AMPA. We conclude that motor alterations induced by chronic 4-AP infusion in the spinal cord in vivo is due to ionotropic glutamate receptor overactivation and that blockade of GABAergic neurotransmission induces motor neuron death under chronic conditions. These results shed light on the role of glutamatergic and GABAergic neurotransmission in the regulation of motor neuron excitability in the spinal cord.